Current Regulatory Requirements for Biosimilars in Six Member Countries of BRICS-TM: Challenges and Opportunities - Rahalkar, Hasumati; Sheppard, Alan; Santos, Gustavo Mendes Lima; Dasgupta, Chitralekha; Perez-Tapia, Sonia Mayra; Lopez-Morales, Carlos A.; Salek, Sam (Frontiers in Medicine, 2021)
Background: The aim of the study was to identify, interpret, and compare the current perspectives of regulatory agencies in six member countries of BRICS-TM (Brazil, Russia, India, China, South Africa, Turkey, and Mexico) on the different criteria used for biosimilar development and marketing authorisation process. Methods: A semi-quantitative questionnaire was developed covering the organisation of agency, biosimilar development criteria and marketing authorisation process and sent to seven regulatory agencies covering the BRICS-TM countries. All data was kept anonymous and confidential. Data processing and analysis was carried out; descriptive statistics were used for quantitative data and content analysis was employed to generate themes for qualitative data. Results: Out of the seven regulatory agencies included in the study, six representatives provided the responses. The perspectives of these six regulatory agencies varied on a number of aspects relating to the review criteria for biosimilar development and licencing process. The most prevalent model for data assessment is the “full review” of a marketing authorisation application. There is lack of a standard approach across the agencies on sourcing of the reference biological product, in vivo toxicity studies and confirmatory clinical studies. Most agencies restrict interaction with biosimilar developers and any scientific advice is non-binding. The marketing authorisation approval depends on scientific assessment of the dossier, sample analysis and GMP certification. The agencies do not issue any public assessment report specifying the summary basis of biosimilar approval. Conclusion: Regulatory agencies across the six emerging economies are steadily improving the regulatory mechanism in the area of biosimilars. However, there remains scope for increasing the effectiveness and efficiency of the processes by encouraging open and transparent interaction with developers, adopting a flexible approach toward accepting advanced analytical data in lieu of clinical studies and enhancing regulatory reliance amongst agencies. This will help to simplify the new biosimilar development programmes and make them more cost-effective.